2017
DOI: 10.1080/13880209.2017.1357735
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxant properties of Vernonia amygdalina ethanol extract and its possible mechanism

Abstract: Context:Vernonia amygdalina Del. (VA) (Asteraceae) is commonly used to treat hypertension in Malaysia.Objective: This study investigates the vasorelaxant mechanism of VA ethanol extract (VAE) and analyzes its tri-step FTIR spectroscopy fingerprint.Materials and methods: Dried VA leaves were extracted with ethanol through maceration and concentrated using rotary evaporator before freeze-dried. The vasorelaxant activity and the underlying mechanisms of VAE using the cumulative concentration (0.01–2.55 mg/mL at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 31 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…β 2 -adrenoreceptor, a GPCR, only exists on the membrane of VSMCs. This receptor passes through the GPCR/AC pathway, which catalyses the breakdown of ATP into cAMP and subsequently causes vasodilation ( Ch'ng et al, 2017 ). Propranolol, a nonselective β 2-adrenergic receptor inhibitor, eventually causes vasoconstriction through inhibiting this channel.…”
Section: Vasodilation Mechanism Of Tmps and Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…β 2 -adrenoreceptor, a GPCR, only exists on the membrane of VSMCs. This receptor passes through the GPCR/AC pathway, which catalyses the breakdown of ATP into cAMP and subsequently causes vasodilation ( Ch'ng et al, 2017 ). Propranolol, a nonselective β 2-adrenergic receptor inhibitor, eventually causes vasoconstriction through inhibiting this channel.…”
Section: Vasodilation Mechanism Of Tmps and Natural Productsmentioning
confidence: 99%
“…However, its effects were significantly reduced by endothelial removal, TEA, 4-AP, BaCl 2 , glibenclamide, L-NAME (eNOS blocker), methylene blue (cGMP inhibitor), indomethacin (COX inhibitor), atropine (muscarinic receptor inhibitor) and propranolol (β 2 -adrenoreceptor inhibitor). Hence, the effect of VAE was related with the NO/cGMP/PGI2 pathways, Ca 2+ /K + channels or β 2 -adrenergic receptor ( Ch’ng et al, 2017 ). Additionally, VA (i.v.…”
Section: Traditional Medicinal Plants With Vasodilation In mentioning
confidence: 99%
“…Generally, there are three key information that could be speculated from the findings presented above, the results of these research clearly presented the competency of combined drugs over single drugs in terms of exhibiting vasodilatory effects, the orthogonal stimulus-response compatibility study approach could be used to formulate TCM formula in terms of treating complex diseases, and the crude extracts of the herbs could provide promising therapeutic effects rather than single compounds due to holistic mechanisms of actions whilst providing cost-effective beneficial from the commercial viewpoint as compared to pure compound [ 21 24 ].…”
Section: Resultsmentioning
confidence: 95%
“…The production of these second messengers are strictly dependent on the activation of various types of the receptors that are located on the vasculature including EDRFs, enzyme-linked, G-protein-coupled, and channel-linked receptors. According to literatures, the vasodilative receptors are more frequently being included in the experimental study on mechanisms of actions of test compounds rather than vasoconstrictive receptors [ 86 , 87 , 88 , 89 , 90 , 91 ]. Therefore, following the current trend of pharmacological research, all the vasodilation-mediated receptors pathways that should be investigated during the mechanisms of actions study of test compounds were suggested at this section.…”
Section: General Integration Of Vasodilative Receptorsmentioning
confidence: 99%
“…The activation of IP 3 R is strictly dependent on the activation of G q α-protein-coupled receptors, which allows the Ca 2+ ions released from the store of sacroplasmic reticulum into the cytosol. Therefore, all these channel-linked pathways should be investigated during the mechanisms of actions study on vasodilatory effects of test compounds [ 5 , 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: General Integration Of Vasodilative Receptorsmentioning
confidence: 99%